Evaluating fence-end treatments for migratory amphibians - Harman, Kristine E.; Omlor, Kadie; Popescu, Viorel (Frontiers in Ecology and Evolution, 2023)
Migratory amphibians require movements to complete their biphasic life cycle, often across altered landscapes fragmented by roadways, which can have severe consequences on their populations. To manage this threat, transportation agencies have begun to implement exclusion fencing to separate natural areas from the roadway to prevent wildlife-vehicle collisions. Although fences are an effective conservation tool, the tendency of animals to access the road by circumventing the fence ends, known as the fence-end effect, threatens to jeopardize management efforts to reduce road associated mortality. One strategy to lessen the impacts of the fence-end effect is to construct fence-end treatments to block amphibian movement and guide the animals to safe crossing locations. By using experimental fence arenas, we examined how nine amphibian species responded to two alternative fence-end structures: horizontal v-shape and perpendicular fence-end treatments. Using a generalized linear model framework, we found both fence-end treatments to be an effective strategy to reduce the impacts of the fence-end effect, with our predictor variable, fence-end treatment, explaining most of the variation in amphibian response. Structure effectiveness also started to improve by 20% with each 7°C increase in temperature, however, this was not significant. Despite these promising findings, we also found for each additional 312 s an amphibians spent attempting to navigate around the experimental fence resulted in a 25% decline in structure effectiveness, suggesting longer fences are not an adequate protection measure to combat the fence-end effect for amphibians. In addition, Anaxyrus americanus was not found to differ in their response, performing equally well to both experimental fence-end treatments. In contrast, Rana spp., Pseudacris crucifer, and Notopthalmus viridescens showed a greater response to the horizontal v-shape fence-end treatment compared to the perpendicular fence-end treatment. Variation in response for Ambystoma spp. could not be detected due to a small sample size; however, no individuals responded positively to the perpendicular fence-end treatment. Guidelines for amphibian fences should continue to incorporate fence-end treatments into the design and implementation to mitigate for the fence-end effect, and preferably angle the fence-ends inward in the horizontal v-shape pattern with the fence ends diagonal to the road for migratory amphibians.